KONTRADIKSI PENGATURAN SITA ASET MILIK BUMD BERBENTUK PERSEROAN DAERAH - Muhammad Iswan; Novita Sari; Jamaludin Ghafur (Supremasi Hukum: Jurnal Penelitian Hukum, 2024)
This research aims to elaborate on the reasons for the contradictions in legal arrangements regarding confiscation of assets owned by regional companies and how the legal arrangements for confiscation of assets owned by regional companies should be. This research is a type of juridical-normative research. The primary legal materials used are the State Finance Law, the State Treasury Law and the Regional Government Law and PP BUMD. Coupled with Law no. 5 of 1962 concerning regional companies. The research was conducted by inventorying regulations relating to BUMD in the form of regional companies. Legal materials that have been inventoried are then analyzed using the prescription method. The results showed that the contradiction in the regulation of conflict of assets of regional companies boils down to the use of the term regional company in the State Finance Law. The conceptual reference to regional companies in Law No. 5 of 1962 is no longer in line with the form of regional companies that have been transformed into BUMD based on the Regional Government Law and PP BUMD. Thus, Article 50 of the State Treasury Law does not apply to assets that are separated and managed independently by regional companies. In addition, the regulation on configuration of assets of regional companies must begin with an amendment to the State Finance Law, followed by the State Treasury Law. Regulations on the confiscation of assets of regional companies must be carried out to provide justice for every legal entity and the wealth of private legal entities in Indonesia.